2012
DOI: 10.5664/jcsm.1670
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variability in Epidemiological Studies of Sleep Using Repeated Nights of In-Home Polysomnography: SWAN Sleep Study

Abstract: Study Objective: To quantify sources of night-to-night variability. Methods: This project was conducted in 285 middle-aged African American, Caucasian, and Chinese women from the Study of Women's Health Across the Nation (SWAN) Sleep Study living in Chicago, the Detroit area, Oakland, and Pittsburgh. The study used 3 repeated nights of in-home polysomnography (PSG) measures. Night 1 data included assessment of sleep staging, sleep apnea, and periodic limb movements, while Nights 2 and 3 focused on sleep stagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
(24 reference statements)
5
31
0
Order By: Relevance
“…Compared with the selfreported SOL, the actigraphic SOL is closer in value to the results of polysomnography [21]. However, the night-to-night variability of an objectively measured sleep profile is not negligible [22]. Therefore, similarity between the results for the subjective SOL and objective SOL in the present study strengthens the evidence from the objective SOL.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with the selfreported SOL, the actigraphic SOL is closer in value to the results of polysomnography [21]. However, the night-to-night variability of an objectively measured sleep profile is not negligible [22]. Therefore, similarity between the results for the subjective SOL and objective SOL in the present study strengthens the evidence from the objective SOL.…”
Section: Discussionsupporting
confidence: 90%
“…This effect is present in repeated attended PSG [35][36][37], but it is generally not present at home [35,38]. However, in the recent large cohort of the Study of Women's Health Across the Nation (SWAN), Zheng et al [39] recorded three consecutive nights at home. A first-night effect was clearly observed as sleep efficiency, total sleep time, sleep latency, percentage REM sleep, and wake after sleep onset improved between nights 1 and 2 but not between nights 2 and 3.…”
Section: Discussionmentioning
confidence: 98%
“…The simulation showed that the intraclass correlation coefficient (ICC) was 0.90 using three weeks of data (21 days) and 0.80 using second week and third week data only (14 days). Another simulation using PSG data showed that about 125 women gave 95% coverage probability (i.e., the proportion of the simulation runs in which the estimated interval contained the true value of parameter over all the simulation runs) to detect “night” effects 30 . This suggests that the analytical dataset (163 women with three weeks data) was of sufficient sample size to minimize the estimation bias due to data loss by excluding some ineligible women and first week data.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized data were then segmented into four 7-day weekly units. Information from the first week (days ≤7) were not included in analyses as other components of the protocol, such as habituating to overnight sleep assessments, may have disturbed actigraphy-assessed sleep 30 .…”
Section: Methodsmentioning
confidence: 99%